Streptomyces exploration is triggered by fungal interactions and volatile signals - Stephanie E Jones; Louis Ho; Christiaan A Rees; Jane E Hill; Justin R Nodwell; Marie A Elliot (eLife, 2017)
It has long been thought that the life cycle of Streptomyces bacteria encompasses three developmental stages: vegetative hyphae, aerial hyphae and spores. Here, we show interactions between Streptomyces and fungi trigger a previously unobserved mode of Streptomyces development. We term these Streptomyces cells ‘explorers’, for their ability to adopt a non-branching vegetative hyphal conformation and rapidly transverse solid surfaces. Fungi trigger Streptomyces exploratory growth in part by altering the composition of the growth medium, and Streptomyces explorer cells can communicate this exploratory behaviour to other physically separated streptomycetes using an airborne volatile organic compound (VOC). These results reveal that interkingdom interactions can trigger novel developmental behaviours in bacteria, here, causing Streptomyces to deviate from its classically-defined life cycle. Furthermore, this work provides evidence that VOCs can act as long-range communication signals capable of propagating microbial morphological switches.